Transport Characteristics of Interfacial Charge in SiC Semiconductor–Epoxy Resin Packaging Materials - Chi Chen; Jiaxing Li; Xia Wang; Kai Wu; Chuanhui Cheng; Chuang Wang; Yuwei Fu (Frontiers in Chemistry, 2022)
The silicon carbide (SiC) wide bandgap (WBG) semiconductor power device has been widely applied for its excellent properties. However, the charge accumulated in the interface of SiC semiconductor-related insulation packaging may lead to serious material performance degradation and failure, threatening the reliability and operation life of power devices. In this research, interface charge accumulation characteristics of SiC–epoxy resin double-layered material were investigated, and space charge injection, transport, and accumulation mechanisms, as well as the related temperature effect for the SiC–epoxy resin under polarization and depolarization conditions, were studied by the pulsed electro-acoustic (PEA) technique. The results show that a charge peak appears between the SiC–epoxy resin interface, which shows the same polarity as the SiC side electrode. Charge injects from the SiC electrode, transports along with the SiC semiconductor bulk due to the high mobility, and is blocked by the interface barrier. In addition, under high temperature and high electrical stress conditions, obvious charge accumulation occurs inside the epoxy resin bulk, which was captured by the deep traps. The charge accumulation of the SiC-insulation packaging material can influence the operation of the power device and should attract more attention.